2014
DOI: 10.3109/02770903.2013.876649
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of asthma control among children in Saudi Arabia

Abstract: In addition to knowledge, socioeconomic factors, such as family income, household crowding, and the number of siblings are associated with asthma control among children in Saudi Arabia. Further research is needed to investigate the role of these factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 31 publications
5
32
1
Order By: Relevance
“…Almost all the caregivers (97.5%) were the mothers of the children. The sociodemographic characteristics and other characteristics of the study population are listed in Table 1 [10].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Almost all the caregivers (97.5%) were the mothers of the children. The sociodemographic characteristics and other characteristics of the study population are listed in Table 1 [10].…”
Section: Resultsmentioning
confidence: 99%
“…Pearson's chi-square or Fisher's exact tests were used to analyze differences in the responses to each question between groups with controlled and uncontrolled asthma. The results of a multivariate regression analysis have been presented elsewhere [10].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1,2) Uncontrolled asthma may considerably decrease the quality of life for patients and their families. (2) Some reports suggested that the prevalence of asthma is increasing globally. (1) The prevalence of asthma across all the Middle East, especially the Gulf region is also increasing.…”
mentioning
confidence: 99%
“…Current advancements in the knowledge and availability of contemporary medicine can help clinicians effectively control asthma when patients adhere to their treatment plans. [8] However, even in developed countries, 40-70% of patients have uncontrolled asthma [9,10]. Similarly, recent studies have shown that the majority of asthma patients in Saudi Arabia have uncontrolled asthma, with significantly higher levels of uncontrolled asthma among women (77.0% vs.…”
Section: Introductionmentioning
confidence: 97%